Highly mixed silicon-based negative electrode sheet, lithium ion battery and preparation method

CN120637388BActive Publication Date: 2026-10-30XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510802858.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2026-10-30
Estimated Expiration
2045-06-16

AI Technical Summary

Technical Problem

然而,硅负极在充放电过程中的体积变化会导致硅材料粉化并与集流体脱离,使得负极导电性变差,进而导致安全问题、容量损失和有限的电池寿命周期

Benefits of technology

[0052]1、本发明提供了一种高掺混硅基负极片的制备方法,得到含有梯度分布复合负极活性材料层的负极片,梯度分布的复合负极活性材料层在靠近SEI膜的一侧硅的含量较高,这使得在放电过程中靠近SEI膜侧的硅较石墨先脱锂,能在一定程度上提高硅的脱锂深度,提高了电池的放电容量和能量密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637388B_ABST
    Figure CN120637388B_ABST
Patent Text Reader

Abstract

The application provides a high-mixing silicon-based negative plate, a lithium ion battery and a preparation method, relates to the technical field of lithium ion batteries, and comprises a current collector, a composite negative material layer and a graphite negative active material layer; the current collector is coated with the composite negative material layer on both sides; the composite negative material layer is coated with the graphite negative active material layer; wherein the composite negative material layer comprises a first graphite active material and a silicon-based negative material; along the direction away from the current collector, the mass fraction of the first graphite active material decreases from 75% to 95% to 5% to 25%, and the mass fraction of the silicon-based negative material increases from 5% to 25% to 75% to 95%. The application can improve the delithiation depth of silicon, effectively improve the energy density of the battery and relieve the volume expansion of the silicon-based negative battery in the cycle process, and improves the initial coulomb efficiency and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a highly mixed silicon-based anode sheet, a lithium-ion battery, and a preparation method thereof. Background Technology

[0002] In recent years, the demand for energy storage technology has grown rapidly, placing higher demands on the high energy / power density, safety, and durability of lithium-ion batteries. Silicon or silicon-containing materials are considered one of the most promising candidates for next-generation lithium-ion battery anodes due to their ultra-high theoretical capacity, low cost, and abundant sources. However, the volume change of silicon anodes during charge and discharge processes can lead to silicon material pulverization and detachment from the current collector, resulting in poor conductivity of the anode and consequently safety issues, capacity loss, and limited battery life. Currently, commercially available Si / graphite composite batteries can provide higher energy densities, and the addition of graphite can alleviate the volume effect of the electrode to some extent. However, as the Si content increases, the mixed anode potential gradually increases, leading to a decrease in the overall battery potential and power density, and also reducing the battery's initial coulombic efficiency and cycle stability to some extent.

[0003] In view of this, this invention is hereby proposed. Summary of the Invention

[0004] The purpose of this invention is to provide a highly mixed silicon-based anode sheet, a lithium-ion battery, and a preparation method. This invention designs a gradient distribution of the content of the first graphite active material and the content of the silicon-based anode material in the composite anode material layer. This invention can improve the delithiation depth of silicon, effectively increase the energy density of the battery, alleviate the volume expansion of the silicon-based anode battery during cycling, and improve the initial coulombic efficiency and cycle stability of the battery.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] This invention provides a highly doped silicon-based anode sheet, comprising a current collector, a composite anode material layer, and a graphite anode active material layer;

[0007] The current collector is coated with a composite negative electrode material layer on both sides;

[0008] The composite anode material layer is coated with a graphite anode active material layer;

[0009] The composite anode material layer includes a first graphite active material and a silicon-based anode material.

[0010] Along the direction away from the current collector, with the total mass of the first graphite active material and the silicon-based anode material as 100%, the mass fraction of the first graphite active material decreases from 75%-95% to 5%-25%, and the mass fraction of the silicon-based anode material increases from 5%-25% to 75%-95%.

[0011] Furthermore, based on the above technical solution, the composite anode material layer comprises 10-90 parts of first graphite active material and 10-90 parts of silicon-based anode material by mass.

[0012] And / or, the particle size distribution of the first graphite active material is: D10 = 3.0 to 7.0 μm, D50 = 12.0 to 18.0 μm, D90 = 30.0 to 35.0 μm, and the true density is 2.20 g / cm³. 3 Up to 2.26 g / cm 3 ;

[0013] And / or, the silicon-based anode material has the following particle size distribution: D10 = 2.0 to 5.5 μm, D50 = 6.0 to 10.5 μm, D90 = 12.0 to 16.0 μm, and a true density of 1.50 g / cm³. 3 Up to 2.10 g / cm 3 ;

[0014] And / or, the graphite negative electrode active material layer includes a second graphite active material, the second graphite active material being a fast-charging graphite active material, the fast-charging graphite active material including natural graphite particles or artificial graphite particles with a fast-charging capability of 4-6C.

[0015] The specific capacity of both the first and second graphite active materials is 340-360 mAh / g;

[0016] The particle size distribution of the second graphite active material is: D10 = 3.0 to 8.5 μm, D50 = 8.0 to 12.0 μm, D90 = 16.0 to 24.1 μm, and the true density is 2.24 g / cm³. 3 Up to 2.26 g / cm 3 .

[0017] Furthermore, based on the above technical solution, the silicon-based material includes at least one of nano-silicon, micron-silicon, porous silicon, amorphous silicon, silicon alloy, silicon oxide compound, or silicon-carbon composite material.

[0018] And / or, the first graphite active material includes natural graphite particles or artificial graphite particles with a fast charging capability of 1.2-2.5C;

[0019] And / or, the current collector comprises copper foil;

[0020] And / or, the thickness of the highly doped silicon-based anode sheet is 85-100 μm;

[0021] And / or, the thickness of the current collector is 6 μm;

[0022] And / or, the thickness of the composite negative electrode material layer is 60-130 μm;

[0023] And / or, the thickness of the graphite anode active material layer is 10-20 μm.

[0024] The present invention also provides a method for preparing a highly doped silicon-based anode sheet as described above, comprising the following steps:

[0025] S1: Mix the first graphite active material and the silicon-based anode material evenly to obtain a composite anode material; add a first conductive agent, a first binder, a second conductive agent, and a second binder to the composite anode material and disperse them to obtain a first anode slurry;

[0026] S2: Place the aqueous binder in deionized water and stir to obtain a negative electrode solution; add a first conductive agent, a second graphite active material, and a second binder to the negative electrode solution and disperse them to obtain a second negative electrode slurry;

[0027] S3: The first negative electrode slurry is coated on the upper and lower surfaces of the current collector, and then dried, rolled, and shaped to obtain a negative electrode sheet coated with a composite negative electrode material layer; then the second negative electrode slurry is coated on the upper and lower surfaces of the negative electrode sheet coated with the composite negative electrode material layer, and then dried, rolled, and die-cut to obtain a highly mixed silicon-based negative electrode sheet.

[0028] Furthermore, based on the above technical solution, step S1 includes: mixing the first graphite active material and the silicon-based anode material evenly to obtain a composite anode material; sequentially adding the first conductive agent, the first binder, the second conductive agent and deionized water to the composite anode material, dispersing it at high speed, then adding the second binder, dispersing it evenly to obtain the first anode slurry;

[0029] Step S2 includes: placing an aqueous binder in deionized water and stirring to obtain a negative electrode solution; adding a first conductive agent to the negative electrode solution and dispersing it at high speed to obtain a negative electrode conductive adhesive; adding a second graphite active material to the negative electrode conductive adhesive and dispersing it at high speed, then adding a second binder and dispersing it evenly to obtain a second negative electrode slurry.

[0030] Furthermore, based on the above technical solution, the first conductive agent includes one or more of conductive carbon black, acetylene black, and Ketjen black;

[0031] And / or, the first adhesive comprises a propylene polymer or a styrene-butadiene rubber adhesive;

[0032] And / or, the second conductive agent includes one or more of single-walled carbon nanotubes, carbon fibers, and graphene;

[0033] And / or, the second adhesive includes styrene-butadiene rubber-based adhesives;

[0034] And / or, the aqueous binder includes carboxymethyl cellulose;

[0035] And / or, in step S1, the amount of the first conductive agent added is 0.5%-1.0% of the mass of the composite negative electrode material;

[0036] And / or, in step S1, the amount of the first binder added is 2.3%-6% of the total mass of the first conductive agent and the composite negative electrode material;

[0037] And / or, in step S1, the amount of the second conductive agent added is 0.05%-0.1% of the total mass of the first conductive agent and the composite negative electrode material;

[0038] And / or, in step S1, the amount of the second binder added is 1.0-2.5% of the total mass of the first conductive agent, the second conductive agent, the first binder, deionized water and the composite negative electrode material;

[0039] And / or, in steps S1 and S2, the high-speed dispersion rotation speed is 2000-4000 rpm and the time is 5-10 min.

[0040] Furthermore, based on the above technical solution, the viscosity of the first negative electrode slurry is 4000-8000 mPa·s, and the solid content is 40%-65%.

[0041] And / or, the viscosity of the second negative electrode slurry is 2500-4000 mPa·s, and the solid content is 35%-45%; in step S2, the solid content of the negative electrode adhesive is 1.0-2.5%;

[0042] And / or, in step S2, the amount of the first conductive agent added accounts for 0.5-2.0% of the mass of the negative electrode adhesive;

[0043] And / or, in step S2, the amount of the second graphite active material added accounts for 95.3%-96.2% of the mass of the negative electrode conductive adhesive;

[0044] And / or, in step S2, the amount of the second binder added accounts for 1.6-2.5% of the total mass of the second graphite active material and the negative electrode conductive adhesive;

[0045] And / or, in step S3, the coating surface density of the first negative electrode slurry is 86-190 g / cm³.2 The drying temperature of the first negative electrode slurry is 60-80℃;

[0046] And / or, in step S3, the coating surface density of the second negative electrode slurry is 35-45 g / cm³. 2 The drying temperature of the first negative electrode slurry is 70-85℃.

[0047] The present invention also provides a lithium-ion battery, comprising a positive electrode, a highly mixed silicon-based negative electrode as described above, a separator, an electrolyte, and a casing.

[0048] The present invention also provides a method for preparing the lithium-ion battery as described above, comprising the following steps:

[0049] The positive electrode sheet prepared from the positive electrode material and the above-mentioned highly mixed silicon-based negative electrode sheet are stacked, assembled, baked, injected with electrolyte, formed, and capacity tested in sequence according to the separator-negative electrode-separator-positive electrode to produce a highly mixed silicon-based negative electrode lithium-ion battery.

[0050] Furthermore, based on the above technical solution, the formation process includes: charging at 0.1-0.5C for 7-24 minutes, resting for 5 minutes, charging at 0.1-0.5C for 117-127 minutes, and achieving a formation SOC of 35%-40%.

[0051] The present invention provides a highly doped silicon-based anode sheet, a lithium-ion battery, and a preparation method thereof, with the following beneficial effects:

[0052] 1. This invention provides a method for preparing a highly mixed silicon-based negative electrode sheet, which yields a negative electrode sheet containing a gradient-distributed composite negative electrode active material layer. The gradient-distributed composite negative electrode active material layer has a higher silicon content on the side closer to the SEI film. This causes the silicon on the side closer to the SEI film to be delithiated before graphite during discharge, which can improve the delithiation depth of silicon to a certain extent and improve the discharge capacity and energy density of the battery.

[0053] 2. The negative electrode sheet provided by the present invention also includes a graphite negative electrode active material layer, which enables the formation of a stable and tough SEI film during the formation process, effectively alleviating the problems of SEI deformation, cracking and regeneration caused by volume expansion during the cycling process of silicon-based negative electrode lithium-ion batteries; the silicon-based material with a high content is in the middle of the graphite material, and the graphite has high lubricity. After the silicon-based material expands due to lithium intercalation, the middle layer is squeezed to the outer graphite layer and partially embedded in the graphite layer structure. Under high pressure, it can buffer the large amount of stress brought by silicon, thereby reducing the overall expansion rate of the electrode.

[0054] 3. The present invention also provides a method for preparing a high-energy-density lithium-ion battery, which yields a highly mixed silicon-based anode lithium-ion battery with high initial coulombic efficiency, low expansion, and long cycle life. Attached Figure Description

[0055] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0056] Figure 1 A schematic diagram of a simulated structure of one side of a highly doped silicon-based anode sheet provided by the present invention;

[0057] Icon:

[0058] 1. Current collector; 2. Composite anode material layer; 2-1. First graphite active material; 2-2. Silicon-based anode material; 3. Graphite anode active material layer. Detailed Implementation

[0059] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention. Process parameters not specifically specified in the following embodiments are generally performed under conventional conditions.

[0060] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0061] According to a first aspect of the present invention, a highly doped silicon-based anode sheet is provided, comprising a current collector 1, a composite anode material layer 2, and a graphite anode active material layer 3;

[0062] The current collector 1 is coated with a composite negative electrode material layer 2 on both sides;

[0063] The composite negative electrode material layer 2 is coated with a graphite negative electrode active material layer 3;

[0064] The composite anode material layer includes a first graphite active material 2-1 and a silicon-based anode material 2-2.

[0065] Along the direction away from the current collector, with the total mass of the first graphite active material 2-1 and the silicon-based anode material 2-2 as 100%, the mass fraction of the first graphite active material 2-1 decreases from 75%-95% (e.g., 78%, 80%, 82%, 85%, 87%, 90%, 93%, etc.) to 5%-25% (e.g., 7%, 10%, 15%, 20%, 23%, etc.), and the mass fraction of the silicon-based anode material 2-2 increases from 5%-25% (e.g., 7%, 10%, 15%, 20%, 23%, etc.) to 75%-95% (e.g., 78%, 80%, 82%, 85%, 87%, 90%, 93%, etc.).

[0066] Specifically, along the direction away from the current collector, the content of the first graphite active material and the content of the silicon-based anode material exhibit a gradient distribution, with the content of the first graphite active material gradually decreasing and the content of the silicon-based anode material gradually increasing. This invention can improve the delithiation depth of silicon, effectively increase the energy density of the battery, alleviate the volume expansion of the silicon-based anode battery during cycling, and improve the battery's initial coulombic efficiency and cycle stability.

[0067] Specifically, a thin layer of graphite anode active material is coated on the surface of the composite anode active material layer. This material layer mainly serves as a carrier for the precipitated SEI film. Graphite has high lubricity, and after the silicon-based material expands due to lithium intercalation, it is squeezed outwards and partially embedded in the graphite layer structure. Under high pressure, it can buffer the large amount of stress brought by silicon, thereby reducing the overall expansion rate of the electrode. The SEI film formed by high-rate formation has strong flexibility and is strong enough, effectively alleviating the problems of SEI deformation, cracking and regeneration caused by volume expansion during the cycling process of silicon-based anode lithium-ion batteries. During discharge, the potential of the negative electrode gradually increases. The delithiation potential of graphite is lower than that of silicon. Graphite delithigates first, followed by silicon. Generally, there are still some unreleased lithium ions on the silicon negative electrode in the low voltage range. This invention utilizes a gradient electrode design to match short-time high-rate formation. Due to the concentration polarization of lithium ion diffusion, silicon near the SEI film side can delithigate more lithium ions during discharge, which can improve the delithiation depth of silicon to a certain extent and improve the discharge capacity and energy density of the battery.

[0068] As an optional embodiment of the present invention, the composite anode material layer comprises, by weight, 10-90 parts of a first graphite active material (e.g., 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, etc.) and 10-90 parts of silicon-based anode material (e.g., 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, etc.).

[0069] Specifically, due to the gradient distribution of the composite negative electrode active material layer and the coating of a graphite negative electrode active material layer on the surface of the composite negative electrode active material layer, this material layer is relatively thin and mainly serves as a carrier for the precipitated SEI film. Graphite has high lubricity, and after the silicon-based material expands due to lithium intercalation, it is squeezed outwards by the graphite layer and partially embedded in the graphite layer structure. Under high pressure, it can buffer the large amount of stress brought by silicon, thereby reducing the overall expansion rate of the electrode. The SEI film formed by high-rate formation has strong flexibility and is strong enough, effectively alleviating the problems of SEI deformation, cracking and regeneration caused by volume expansion during the cycling process of silicon-based negative electrode lithium-ion batteries. Therefore, even if the content of silicon-based negative electrode material is too high, this invention can alleviate the expansion to a certain extent.

[0070] As an optional embodiment of the present invention, the particle size distribution of the first graphite active material is: D10 = 3.0 to 7.0 μm (e.g., 4 μm, 5 μm, 6 μm, etc.), D50 = 12.0 to 18.0 μm (e.g., 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, etc.), particle size D90 = 30.0 to 35.0 μm (e.g., 31 μm, 32 μm, 33 μm, 34 μm, etc.), and true density is 2.20 g / cm³. 3 Up to 2.26 g / cm 3 (e.g., 2.21g / cm) 3 2.22 g / cm 3 2.23 g / cm 3 2.24 g / cm 3 2.25g / cm 3 wait);

[0071] The silicon-based anode material has the following particle size distribution: D10 = 2.0 to 5.5 μm (e.g., 3 μm, 4 μm, 5 μm, etc.), D50 = 6.0 to 10.5 μm (e.g., 7 μm, 8 μm, 9 μm, 10 μm, etc.), and D90 = 12.0 to 16.0 μm (e.g., 13 μm, 14 μm, 15 μm, etc.), with a true density of 1.50 g / cm³. 3 Up to 2.10 g / cm 3 (e.g., 1.6g / cm) 3 1.7g / cm 3 1.8g / cm 3 1.9g / cm 3 2.0g / cm 3 wait).

[0072] Specifically, this invention utilizes the density difference between silicon-based materials and graphite active materials, as well as the difference in solvent evaporation rate with temperature, to form a composite negative electrode active material layer with a non-uniform gradient distribution. The density of graphite is greater than that of silicon-based materials, and the silicon-based materials in the coating tend to diffuse to the electrode surface. Therefore, by controlling the drying temperature and slurry solid content, the concentration of graphite active materials from the current collector to the electrode surface is reduced, while the concentration of silicon-based materials from the current collector to the electrode surface is increased.

[0073] Furthermore, larger-particle-size graphite has a higher tap density, meaning it can accommodate more active material in the same volume, thus increasing the volumetric energy density of the battery. Large-particle-size graphite also has relatively low slurry viscosity, which helps reduce coating difficulty and simplifies the coating process. Large-particle-size graphite can form denser electrodes, thereby increasing compaction density and battery energy density. The size of the graphite particles affects the initial charge-discharge efficiency. Large-particle-size graphite, due to its higher compaction density, can more effectively accommodate lithium ions, thus improving the initial charge efficiency. However, small-particle-size graphite, due to its larger specific surface area, forms a more stable SEI film, thus improving coulombic efficiency. Large-particle-size graphite has relatively good cycle stability, but its higher compaction density may lead to greater battery expansion after prolonged use, affecting cycle life. The particle size of silicon-based anode materials also affects rate performance; smaller-sized silicon particles exhibit better rate performance.

[0074] As an optional embodiment of the present invention, the silicon-based material includes at least one of nano-silicon, micron-silicon, porous silicon, amorphous silicon, silicon alloy, silicon oxide compound or silicon-carbon composite material;

[0075] The first graphite active material includes natural graphite particles or artificial graphite particles with a fast charging capability of 1.2-2.5C (such as 1.4C, 1.6C, 1.8C, 2.0C, 2.2C, 2.4C, etc.);

[0076] The current collector includes copper foil.

[0077] As an optional embodiment of the present invention, the graphite negative electrode active material layer includes a second graphite active material, which is a fast-charging graphite active material. The fast-charging graphite active material includes natural graphite particles or artificial graphite particles with a fast-charging capability of 4-6C (such as 4.2C, 4.4C, 4.6C, 4.8C, 5C, 5.4C, 5.6C, 5.8C, etc.).

[0078] Specifically, the presence of the fast-charging graphite active material layer and the high-rate current formation can form a stable and highly flexible SEI film on the graphite anode surface. The SEI film has sufficient toughness to resist the large volume expansion during silicon lithium intercalation, thereby improving the cycle stability and safety performance of the battery.

[0079] As an optional embodiment of the present invention, the specific capacity of both the first graphite active material and the second graphite active material is 340-360 mAh / g.

[0080] As an optional embodiment of the present invention, the particle size distribution of the second graphite active material is: D10 = 3.0 to 8.5 μm (e.g., 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc.), D50 = 8.0 to 12.0 μm (e.g., 9 μm, 9.5 μm, 10 μm, 11 μm, 11.5 μm, etc.), particle size D90 = 16.0 to 24.1 μm (e.g., 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, etc.), and true density is 2.24 g / cm³. 3 Up to 2.26 g / cm 3 (e.g., 2.245g / cm³) 3 2.25g / cm 3 2.255g / cm 3 wait).

[0081] Specifically, the D50 of the second graphite active material is smaller than that of the first graphite active material. Due to its larger specific surface area, the smaller graphite particles will form a more stable SEI film, which will alleviate the SEI cracking and repeated regrowth caused by the lithium intercalation expansion of the silicon-based anode. The smaller the graphite particle size, the larger the specific surface area, which helps to reduce the current density of the electrode, reduce the polarization of the electrode, and provide more lithium ion diffusion channels, thereby shortening the migration path and reducing the diffusion resistance.

[0082] As an optional embodiment of the present invention, the thickness of the highly doped silicon-based anode sheet is 85-100 μm (e.g., 90 μm, 93 μm, 95 μm, 97 μm, etc.);

[0083] The thickness of the current collector is 6 μm;

[0084] The thickness of the composite anode material layer is 60-130μm (e.g., 70μm, 80μm, 90μm, 100μm, 11μm, 120μm, etc.). The thickness of the composite anode material layer is directly related to the amount of graphite and silicon mixed. The higher the silicon content, the smaller the thickness.

[0085] The thickness of the graphite anode active material layer is 10-20 μm (e.g., 12 μm, 14 μm, 16 μm, 18 μm, etc.).

[0086] Specifically, the graphite anode active material layer is relatively thin, and its main function is to form an SEI film and serve as a buffer layer for the expansion of silicon-based particles. The silicon-based material content is highest near the graphite anode active material layer, so there is no need to add silicon-based anode material to the graphite active material layer.

[0087] According to a second aspect of the present invention, a method for preparing a highly doped silicon-based negative electrode as described above is provided, comprising the following steps:

[0088] S1: Mix the first graphite active material and the silicon-based anode material evenly to obtain a composite anode material; add a first conductive agent, a first binder, a second conductive agent, and a second binder to the composite anode material and disperse them to obtain a first anode slurry;

[0089] S2: Place the aqueous binder in deionized water and stir to obtain a negative electrode solution; add a first conductive agent, a second graphite active material, and a second binder to the negative electrode solution and disperse them to obtain a second negative electrode slurry;

[0090] S3: The first negative electrode slurry is coated on the upper and lower surfaces of the current collector, and then dried, rolled, and shaped to obtain a negative electrode sheet coated with a composite negative electrode material layer; then the second negative electrode slurry is coated on the upper and lower surfaces of the negative electrode sheet coated with the composite negative electrode material layer, and then dried, rolled, and die-cut to obtain a highly mixed silicon-based negative electrode sheet.

[0091] Specifically, in step S3 of the present invention, after the first negative electrode slurry and the second negative electrode slurry are coated, they are directly dried without standing and settling. This is because after the graphite and silicon mixed negative electrode is left to stand, the slurry will settle and the binder will float, resulting in uneven distribution of the slurry. After coating and drying, the active material is easy to fall off from the current collector.

[0092] As an optional embodiment of the present invention, step S1 includes: mixing the first graphite active material and the silicon-based anode material evenly to obtain a composite anode material; sequentially adding a first conductive agent, a first binder, a second conductive agent and deionized water to the composite anode material, dispersing it at high speed, then adding the second binder, and dispersing it evenly to obtain a first anode slurry;

[0093] Step S2 includes: placing an aqueous binder in deionized water and stirring to obtain a negative electrode solution; adding a first conductive agent to the negative electrode solution and dispersing it at high speed to obtain a negative electrode conductive adhesive; adding a second graphite active material to the negative electrode conductive adhesive and dispersing it at high speed, then adding a second binder and dispersing it evenly to obtain a second negative electrode slurry.

[0094] As an optional embodiment of the present invention, the first conductive agent includes one or more of conductive carbon black (SP), acetylene black, and Ketjen black;

[0095] The first adhesive includes polyacrylic acid (PAA) or styrene-butadiene rubber (SBR) adhesives;

[0096] The second conductive agent includes one or more of single-walled carbon nanotubes (SWCNTs), carbon fibers, and graphene;

[0097] The second adhesive includes styrene-butadiene rubber (SBR) adhesives;

[0098] The water-based binder includes carboxymethyl cellulose (CMC).

[0099] As an optional embodiment of the present invention, in step S1, the amount of the first conductive agent added is 0.5%-1.0% (e.g., 0.6%, 0.7%, 0.8%, 0.9%, etc.) of the mass of the composite negative electrode material;

[0100] In step S1, the amount of the first binder added is 2.3%-6% (e.g., 3%, 4%, 5%, etc.) of the total mass of the first conductive agent and the composite negative electrode material;

[0101] In step S1, the amount of the second conductive agent added is 0.05%-0.1% (e.g., 0.06%, 0.07%, 0.09%, etc.) of the total mass of the first conductive agent and the composite negative electrode material;

[0102] In step S1, the amount of the second binder added is 1.0-2.5% (e.g., 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, etc.) of the total mass of the first conductive agent, the second conductive agent, the first binder, deionized water, and the composite negative electrode material.

[0103] As an optional embodiment of the present invention, the viscosity of the first negative electrode slurry is 4000-8000 mPa·s (e.g., 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, etc.), and the solid content is 40%-65% (e.g., 45%, 50%, 55%, 60%, etc.).

[0104] The viscosity of the second negative electrode slurry is 2500-4000 mPa·s (e.g., 3000 mPa·s, 3500 mPa·s, 3700 mPa·s, etc.), and the solid content is 35%-45% (e.g., 38%, 40%, 43%, etc.).

[0105] Specifically, the present invention limits the solid content of the first and second negative electrode slurries because a suitable solid content helps the first graphite active material and the silicon-based negative electrode material in the composite negative electrode material layer to form a gradient distribution. Specifically, the higher the solid content of the slurry, the greater the viscosity of the slurry, the worse the fluidity, and the poorer the stability of the slurry. It is difficult for the first graphite active material and the silicon-based negative electrode material to form a gradient distribution effect in the composite negative electrode material layer, and it is easy to diffuse and collapse after coating. In severe cases, it may cause stripes or edge shrinkage on the coating surface. Conversely, the lower the solid content of the slurry, the better the fluidity, but it may cause large fluctuations during coating. This will not only affect the gradient distribution effect in the composite negative electrode material layer, but also make the adhesion of the composite negative electrode material layer to the current collector insufficient. As a result, the prepared battery is prone to bulging and cracking. Furthermore, if the solid content is low, the binder and other components are relatively high, and the film structure formed after drying is not dense enough and is easy to peel off from the current collector.

[0106] As an optional embodiment of the present invention, in steps S1 and S2, the high-speed dispersion speed is 2000-4000 rpm (e.g., 2500 rpm, 3000 rpm, 3500 rpm, etc.), and the time is 5-10 min (e.g., 6 min, 8 min, 9 min, etc.).

[0107] As an optional embodiment of the present invention, in step S2, the solid content of the negative electrode adhesive is 1.0-2.5% (e.g., 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, etc.);

[0108] In step S2, the amount of the first conductive agent added accounts for 0.5-2.0% (e.g., 0.7%, 1%, 1.3%, 1.5%, 1.7%, etc.) of the mass of the negative electrode adhesive;

[0109] In step S2, the amount of the second graphite active material added accounts for 95.3%-96.2% (e.g., 95.5%, 95.7%, 96%, etc.) of the mass of the negative electrode conductive adhesive;

[0110] In step S2, the amount of the second binder added accounts for 1.6-2.5% (e.g., 1.8%, 2.0%, 2.2%, 2.4%, etc.) of the total mass of the second graphite active material and the negative electrode conductive adhesive.

[0111] In an optional embodiment of the present invention, in step S3, the coating surface density of the first negative electrode slurry is 86-190 g / cm³. 2 (e.g., 100g / cm) 2 120g / cm 2 140g / cm 2 160g / cm 2180g / cm 2 The drying temperature of the first negative electrode slurry is 60-80℃ (e.g., 62℃, 65℃, 70℃, 75℃, etc.).

[0112] Specifically, the present invention chooses to dry the first negative electrode slurry at a temperature of 60-80℃ because if the temperature is too high, the solvent evaporates too quickly, and the dense graphite will also be carried away from the current collector by the rapidly evaporating solvent, making it impossible to form a gradient distribution with the silicon-based particles. In addition, excessively high temperatures will cause the electrode to crack. If the temperature is too low, the solvent evaporates slowly, and the low-density silicon particles cannot migrate to the section away from the current collector in time, making it impossible to form a gradient distribution with the graphite.

[0113] In step S3, the surface density of the second negative electrode slurry is 35-45 g / cm³. 2 (e.g., 38g / cm) 2 40g / cm 2 42g / cm 2 44g / cm 2 The drying temperature of the first negative electrode slurry is 70-85℃ (e.g., 72℃, 75℃, 80℃, etc.).

[0114] Specifically, this invention utilizes the density difference between silicon-based materials and graphite active materials, as well as the difference in solvent evaporation rate with temperature, to form a composite negative electrode active material layer with a non-uniform gradient distribution. When the temperature is too high, the solvent evaporation rate increases, and the denser graphite particles will concentrate more near the current collector, while the less dense silicon-based particles will be carried to the surface by the liquid.

[0115] Furthermore, the higher the solid content of the slurry, the greater its viscosity and the worse its fluidity. If the temperature is too low, the graphite and silicon-based anode cannot form a gradient distribution; if the temperature is too high, the electrode is prone to cracking. Conversely, if the solid content of the slurry is low, although the slurry has good fluidity, it may lead to insufficient adhesion of the coating. Because there are fewer solid components and relatively more binders, the film structure formed after drying is not dense enough and is easily peeled off from the current collector.

[0116] According to a third aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode, a highly mixed silicon-based negative electrode prepared by the method described above or by the method described above, a separator, an electrolyte, and a casing.

[0117] According to a fourth aspect of the present invention, a method for preparing a lithium-ion battery as described above is provided, comprising the following steps:

[0118] A high-mixed silicon-based negative electrode lithium-ion battery is produced by stacking, assembling, baking, liquid injection, formation, and capacity testing of a positive electrode sheet prepared from a positive electrode material and a high-mixed silicon-based negative electrode sheet prepared by the above-described preparation method, in the order of separator-negative electrode-separator-positive electrode.

[0119] As an optional embodiment of the present invention, the positive electrode material in the positive electrode sheet is a high-nickel ternary material;

[0120] The diaphragm is a commercially available 12μm PP wet-process diaphragm;

[0121] The electrolyte is a 1 mol / L lithium salt solution.

[0122] The lithium salt is LiPF6, the solvent is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, and the additives include fluoroethylene carbonate (FEC) and vinylene carbonate (VC).

[0123] FEC accounts for approximately 7.0% by weight of the electrolyte, and VC accounts for approximately 3.0% by weight of the electrolyte.

[0124] The formation process includes: placing the battery, which has been immersed in electrolyte for 24 hours, in an environment with a pressure of 280 kPa and a temperature of 45°C, charging at 0.1-0.5C (e.g., 0.2C, 0.3C, 0.4C, etc.) for 7-24 minutes (10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, etc.), resting for 5 minutes, and charging at 0.1-0.5C (e.g., 0.2C, 0.3C, 0.4C, etc.) for 117-127 minutes (120 min, 124 min, 126 min, etc.), resulting in a formation SOC of 35%-40% (e.g., 36%, 37%, 38%, 39%, etc.).

[0125] Specifically, the most critical film-forming stage in the formation process is the first stage of formation. The SEI film formed by high-rate formation in the first stage of formation has strong flexibility and is strong enough, which effectively alleviates the problems of SEI deformation, cracking and regeneration caused by volume expansion during the cycling process of silicon-based negative electrode lithium-ion batteries.

[0126] Furthermore, an excessively high formation rate may loosen the structure of the SEI film, increasing the resistance to lithium ion transport within the SEI film and thus affecting the battery's rate performance. An excessively high formation rate may also cause lithium ions to migrate too quickly between the positive and negative electrodes, resulting in some lithium ions not having enough time to embed into the negative electrode material, thus causing the loss of active lithium, reducing the battery's initial charge-discharge efficiency, and causing capacity decay. In addition, it may also cause excessive side reactions between the electrode materials and electrolyte inside the battery, accelerating the battery's aging process.

[0127] The present invention will now be described in further detail with reference to specific embodiments and comparative examples.

[0128] Example 1

[0129] S1: Artificial graphite particles (fast charging capability of 2.5C, specific capacity of 350mAh / g) and nano-silicon are mixed evenly in a weight ratio of 4:6 to obtain a composite anode material; then, about 0.95% conductive carbon black (SP) based on the weight of the composite anode material is added to the obtained composite anode material and mixed evenly, then about 3% polyacrylic acid (PAA), deionized water and 0.1% single-walled carbon nanotubes (SWCNTs) based on the weight of the above mixed material are added, and the mixture is dispersed at a high speed of 3000rpm for 10min, then about 1.4% styrene-butadiene rubber (SBR) binder based on the weight of the above mixed material is added to the above slurry and dispersed evenly to obtain a first anode slurry. The viscosity of the first anode slurry is 6235mPa·s and the solid content is 52.6%.

[0130] The artificial graphite particles have the following particle sizes: D10 = 5.93 μm, D50 = 12.6 μm, D90 = 31.4 μm, and a true density of 2.24 g / cm³. 3 ;

[0131] The nano-silicon particles have the following dimensions: D10 = 5.21 μm, D50 = 9.62 μm, D90 = 15.88 μm, and a true density of 1.80 g / cm³. 3 .

[0132] S2: A negative electrode solution with a solid content of approximately 1.8% by weight was prepared by adding carboxymethyl cellulose (CMC) as an aqueous binder to deionized water. Approximately 1.0% by weight of a conductive agent containing conductive carbon black (SP) was added to the obtained negative electrode solution and dispersed at high speed to obtain a negative electrode conductive gel. Approximately 95.8% by weight of natural graphite particles (with a fast charging capability of 6C, a specific capacity of 349 mAh / g, particle sizes of D10 = 4.52 μm, D50 = 10.47 μm, D90 = 20.69 μm, and a true density of 2.25 g / cm³) as the negative electrode active material was added to the obtained negative electrode conductive gel.3 The mixture was dispersed at 3000 rpm for 10 minutes. Then, an appropriate amount of deionized water was added to the mixture to adjust its viscosity. Finally, approximately 2.0% of styrene-butadiene rubber (SBR) binder based on the weight of the mixed materials was added to the mixture to obtain a second negative electrode slurry. The viscosity of the second negative electrode slurry was 2936 mPa·s, and the solid content was 37.8%.

[0133] S3: The obtained first negative electrode slurry is uniformly coated onto the upper and lower surfaces of a 6μm thick copper foil using extrusion coating. After drying and roll forming, a negative electrode sheet coated with a composite negative electrode material layer is obtained, with a coating surface density of 100.1 g / cm³. 2 The drying temperature is 65℃; then, the second negative electrode slurry is uniformly coated onto the upper and lower surfaces of the above negative electrode sheet using extrusion coating, with a coating surface density of 40 g / cm³. 2 A heterogeneous gradient highly mixed silicon-based anode sheet with a thickness of 90 μm was obtained by drying at 80℃, rolling, and die-cutting.

[0134] In this process, the mass fraction of the artificial graphite particles in the composite negative electrode material layer is reduced from 85% to 15%, while the mass fraction of nano-silicon is increased from 15% to 85%.

[0135] The thickness of the composite anode material layer is 75 μm;

[0136] The thickness of the graphite anode active material layer is 15 μm.

[0137] Preparation of positive electrode

[0138] A positive electrode adhesive with a solid content of approximately 6% by weight was prepared by mixing polyvinylidene fluoride (PVDF) with the solvent N-methylpyrrolidone (NMP). Approximately 1.1% by weight of conductive carbon black (SP) and 0.5% by weight of multi-walled carbon nanotubes (MWCNTs) were added to the obtained positive electrode adhesive and dispersed at high speed to obtain a positive electrode conductive adhesive. Approximately 97.2% by weight of high-nickel ternary positive electrode material was added to the obtained positive electrode conductive adhesive and dispersed at high speed to obtain a positive electrode slurry with a viscosity of 7250 mPa·s. The above positive electrode slurry was uniformly coated onto the upper and lower surfaces of a 12 μm thick carbon-coated aluminum foil, dried, rolled, and die-cut to obtain a double-sided areal density of 530 g / m². 2 The positive electrode sheet.

[0139] The prepared positive electrode sheet is assembled with the above-prepared highly mixed silicon-based negative electrode sheet to form a lithium-ion battery, including the following steps:

[0140] The above-mentioned positive and negative electrode sheets are stacked, assembled, baked, injected with electrolyte, formed, and capacity tested according to the following processes: separator-negative electrode-separator-positive electrode. The electrolyte concentration is 1 mol / L, the lithium salt is LiPF6, and the solvent is ethylene carbonate (EC) + dimethyl carbonate (DMC) + ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. Additives include fluoroethylene carbonate (FEC) and vinylene carbonate (VC), with FEC accounting for approximately 7.0% by weight and VC accounting for approximately 3.0% by weight. The formation process involves placing the battery, after being immersed in electrolyte for 24 hours, in an environment with a pressure of 280 kPa and a temperature of 45°C, charging at 0.1C for 7 minutes, resting for 5 minutes, and charging at 0.16C for 127 minutes, resulting in a formation SOC of 35%.

[0141] Example 2

[0142] The main difference between this embodiment and Embodiment 1 is that the drying temperature of the first negative electrode slurry is 75°C, while the remaining steps and technical parameters are the same as in Embodiment 1.

[0143] Example 3

[0144] The main difference between this embodiment and Embodiment 1 is that the drying temperature of the first negative electrode slurry is 60°C, while the remaining steps and technical parameters are the same as in Embodiment 1.

[0145] Example 4

[0146] In this example, the surface density of the second negative electrode slurry is 35 g / cm³. 2 The heterogeneous gradient highly doped silicon-based anode sheet with a thickness of 88 μm was obtained by drying at 75°C, rolling, and die-cutting. The remaining steps and technical parameters are the same as in Example 1.

[0147] Example 5

[0148] In this example, the surface density of the second negative electrode slurry is 45 g / cm³. 2 The anode material with a non-homogeneous gradient and high doping of silicon was dried at 83°C, rolled, and die-cut to obtain a thickness of 92 μm. The remaining steps and technical parameters were the same as in Example 1.

[0149] Example 6

[0150] The formation process in this embodiment is as follows: 0.1C charging for 24 minutes, resting for 5 minutes, 0.16C charging for 117 minutes, with a formation SOC of 35%. The remaining steps and technical parameters are the same as in Embodiment 1.

[0151] Example 7

[0152] In this embodiment, the mass ratio of the first graphite active material to the silicon-based anode material is 5:5, and the coating surface density of the first anode slurry is 110 g / m³. 2 The remaining steps and technical parameters are the same as in Example 1.

[0153] Example 8

[0154] In this embodiment, the mass ratio of the first graphite active material to the silicon-based anode material is 7:3, and the coating surface density of the first anode slurry is 90 g / m³. 2 The remaining steps and technical parameters are the same as in Example 1.

[0155] Comparative Example 1

[0156] This comparative example does not use a graphite anode active material layer; it only uses the first anode slurry to prepare the anode sheet. The coating surface density of the composite anode material layer is 120 g / cm³. 2 The remaining steps and technical parameters are the same as in Example 1.

[0157] Comparative Example 2

[0158] The first negative electrode slurry in this comparative example is a pure silicon-carbon composite material, and the coating surface density of the silicon-carbon material layer is 90 g / cm³. 2 The remaining steps and technical parameters are the same as in Example 1.

[0159] Comparative Example 3

[0160] The first negative electrode slurry in this comparative example is a pure graphite active material, and the remaining steps and technical parameters are the same as in Example 1.

[0161] Comparative Example 4

[0162] The formation process used in this comparative example is as follows: 0.01C charging for 60 minutes, resting for 5 minutes, 0.1C charging for 48 minutes, resting for 5 minutes, 0.3C charging for 62 minutes, and the remaining steps and technical parameters are the same as in Example 1.

[0163] Comparative Example 5

[0164] The main difference between this comparative example and Example 1 is that the viscosity of the first negative electrode slurry is 2000 mPa·s and the solid content is 35.2%. The remaining steps and technical parameters are the same as in Example 1.

[0165] Comparative Example 6

[0166] The main difference between this comparative example and Example 1 is that the viscosity of the first negative electrode slurry is 9000 mPa·s and the solid content is 65%. The remaining steps and technical parameters are the same as in Example 1.

[0167] Comparative Example 7

[0168] The main difference between this comparative example and Example 1 is that the drying temperature of the first negative electrode slurry is 100°C, while the remaining steps and technical parameters are the same as in Example 1.

[0169] Comparative Example 8

[0170] In this comparative example, a silicon-based anode material was added to the graphite anode active material layer. The mass ratio of the silicon-based anode material to the second graphite active material was 2:8. The viscosity of the second anode slurry was 3201 mPa·s, and the solid content was 38.5%. The remaining steps and technical parameters were the same as in Example 1.

[0171] Comparative Example 9

[0172] The main difference between this comparative example and Example 1 is that the formation process is as follows: the battery that has been immersed in the electrolyte for 24 hours is placed in an environment with a pressure of 280 kPa and a temperature of 45°C, charged at 0.7C for 7 minutes, rested for 5 minutes, charged at 0.16C for 127 minutes, and the formation SOC is 35%.

[0173] Performance testing

[0174] The electrochemical performance of lithium-ion batteries was tested, and the specific testing methods are as follows:

[0175] 1. Charge the battery at a constant current of 1C at 25℃±2℃ until the battery voltage reaches 4.25V, then switch to constant voltage charging until the current drops to 0.05C and then stop charging. Allow the battery to stand for 1 hour after charging. Discharge the battery at a constant current of 1C at 25℃±2℃ until the battery voltage reaches 2.5V and then stop discharging. Test the capacity retention rate and the full-charge expansion rate of the negative electrode after 200 cycles, and calculate the initial coulombic efficiency.

[0176] Capacity retention rate after 200 cycles = Discharge capacity at the 200th cycle / Discharge capacity at the cell's BOL (Best in Hour) cycle;

[0177] The full-charge expansion rate of the negative electrode sheet = (thickness of the negative electrode sheet after full charge after the 200th cycle - thickness of the negative electrode sheet after full charge of the cell BOL) / (thickness of the negative electrode sheet after full charge of the cell BOL - thickness of the foil).

[0178] Initial coulombic efficiency = cell initial discharge capacity / cell initial charge capacity;

[0179] 2. Cut the obtained negative electrode sheet into small circular pieces with a diameter of 12mm and combine them with lithium sheets to form a button cell. The specific testing method is as follows: 1. Let stand for 5min, 2. 0.1C CC to 5mV, 3. Let stand for 5min, 4. 0.05C CC to 5mV, 5. Let stand for 5min, 6. 0.01C CC to 5mV, 7. Let stand for 5min, 8. 0.1C DC to 2V. Calculate the delithiation specific capacity of the negative electrode sheets of each embodiment and comparative example.

[0180] The results obtained after the test are shown in Table 1 below:

[0181] Table 1

[0182]

[0183]

[0184] As shown in Table 1, Example 1 exhibits a higher lithium removal specific capacity compared to Examples 2 and 3. The drying temperature affects the gradient distribution of graphite and silicon in the composite anode material layer. Higher or lower temperatures result in faster or slower drying rates. Low-density silicon-carbon materials may not migrate to the end furthest from the current collector in time, or high-density graphite may also drift away from the current collector due to the low solvent drying rate. Graphite and silicon may accumulate together, failing to achieve a gradient distribution effect, thus resulting in poor cycle stability. By utilizing a gradient electrode design, the silicon content near the SEI film is greater than the graphite content, allowing silicon to remove more lithium ions and increasing the lithium removal depth. Example 1 has a higher coulombic efficiency than Comparative Example 1 and Examples 4 and 5. Within a certain range, as the size of the fast-charging graphite anode material layer increases, the full-charge expansion rate of the anode sheet decreases, while the coulombic efficiency and 200-cycle capacity retention rate increase. Comparing Examples 1 and 6 with Comparative Example 4, it is shown that the presence of the fast-charging graphite active material layer and high-rate current formation can form a stable and highly flexible SEI film on the graphite anode surface. The SEI film has sufficient toughness to resist the large volume expansion during silicon lithium intercalation, thus improving the cycle stability and safety performance of the battery. Example 1 has a lower full-charge expansion rate of the anode sheet than Comparative Examples 2 and 3, indicating that the mixture of graphite active material and silicon-based anode material can, to a certain extent, mitigate the expansion of the anode sheet and improve cycle stability.

[0185] As can be seen from Table 1, compared with Example 1, Comparative Example 5 has a lower solid content and greater fluidity due to the viscosity of the first negative electrode slurry being 2000 mPa·s and the solid content being 35.2%. This results in a poor gradient distribution effect in the prepared composite negative electrode material layer and insufficient adhesion of the composite negative electrode material layer to the current collector, thus affecting the performance of the battery.

[0186] As can be seen from Table 1, compared with Example 1, Comparative Example 6 has a higher viscosity (9000 mPa·s) and a higher solid content (65%) in the first negative electrode slurry, resulting in poor fluidity.

[0187] Firstly, the graphite active material and silicon-based anode material are difficult to form a gradient distribution effect in the composite anode material layer. They are prone to diffusion and collapse after coating, which in turn affects the performance of the battery.

[0188] As can be seen from Table 1, compared with Example 1, Comparative Example 7 has a higher drying temperature of 100°C for the first negative electrode slurry. The solvent evaporates too quickly, and the dense graphite is also carried away from the current collector by the rapidly evaporating solvent, making it impossible to form a gradient distribution with the silicon-based particles. In addition, the high temperature will cause the electrode to crack, thus affecting the performance of the battery.

[0189] As can be seen from Table 1, compared with Example 1, Comparative Example 8 has a thinner graphite anode active material layer because silicon-based anode material is added to the graphite anode active material layer. After adding silicon-based anode material, it not only fails to buffer the expansion of silicon-based particles in the composite anode material layer, but also aggravates the expansion of silicon-based particles, thereby affecting the performance of the battery.

[0190] As can be seen from Table 1, compared with Example 1, Comparative Example 9 has a larger formation rate in the first stage, which leads to a looser structure of the SEI film and an increased resistance to lithium ion transport in the SEI film, thereby affecting the rate performance of the battery.

[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A highly doped silicon-based anode sheet, characterized in that, It includes a current collector, a composite negative electrode material layer, and a graphite negative electrode active material layer; The current collector is coated with a composite negative electrode material layer on both sides; The composite anode material layer is coated with a graphite anode active material layer; The composite anode material layer includes a first graphite active material and a silicon-based anode material. Along the direction away from the current collector, with the total mass of the first graphite active material and the silicon-based anode material as 100%, the mass fraction of the first graphite active material decreases from 75%-95% to 5%-25%, and the mass fraction of the silicon-based anode material increases from 5%-25% to 75%-95%. The method for preparing the highly doped silicon-based anode sheet includes the following steps: S1: Mix the first graphite active material and the silicon-based anode material evenly to obtain a composite anode material; add a first conductive agent, a first binder, a second conductive agent, and a second binder to the composite anode material and disperse them to obtain a first anode slurry; The viscosity of the first negative electrode slurry is 4000-8000 mPa·s, and the solid content is 40%-65%. S2: Place the aqueous binder in deionized water and stir to obtain a negative electrode solution; add a first conductive agent, a second graphite active material, and a second binder to the negative electrode solution and disperse them to obtain a second negative electrode slurry; S3: The first negative electrode slurry is coated on the upper and lower surfaces of the current collector, and then dried, rolled, and shaped to obtain a negative electrode sheet coated with a composite negative electrode material layer; then the second negative electrode slurry is coated on the upper and lower surfaces of the negative electrode sheet coated with the composite negative electrode material layer, and then dried, rolled, and die-cut to obtain a highly mixed silicon-based negative electrode sheet. The drying temperature of the first negative electrode slurry is 60-80℃.

2. The highly doped silicon-based anode sheet according to claim 1, characterized in that, The composite anode material layer comprises 10-90 parts by weight of a first graphite active material and 10-90 parts by weight of a silicon-based anode material; And / or, the particle size distribution of the first graphite active material is: D10 = 3.0 to 7.0 μm, D50 = 12.0 to 18.0 μm, D90 = 30.0 to 35.0 μm, and the true density is 2.20 g / cm³. 3 Up to 2.26 g / cm 3 ; And / or, the silicon-based anode material has the following particle size distribution: D10 = 2.0 to 5.5 μm, D50 = 6.0 to 10.5 μm, D90 = 12.0 to 16.0 μm, and a true density of 1.50 g / cm³. 3 Up to 2.10 g / cm 3 ; And / or, the graphite negative electrode active material layer includes a second graphite active material, the second graphite active material being a fast-charging graphite active material, the fast-charging graphite active material including natural graphite particles or artificial graphite particles with a fast-charging capability of 4-6C. The specific capacity of both the first and second graphite active materials is 340-360 mAh / g; The particle size distribution of the second graphite active material is: D10 = 3.0 to 8.5 μm, D50 = 8.0 to 12.0 μm, D90 = 16.0 to 24.1 μm, and the true density is 2.24 g / cm³. 3 Up to 2.26 g / cm 3 .

3. The highly doped silicon-based anode sheet according to claim 1, characterized in that, The silicon-based anode material includes at least one of nano-silicon, micron-silicon, porous silicon, amorphous silicon, silicon alloy, silicon oxide compound, or silicon-carbon composite material; And / or, the first graphite active material includes natural graphite particles or artificial graphite particles with a fast charging capability of 1.2-2.5C; And / or, the current collector comprises copper foil; And / or, the thickness of the highly doped silicon-based anode sheet is 85-100 μm; And / or, the thickness of the current collector is 6 μm; And / or, the thickness of the composite negative electrode material layer is 60-130 μm; And / or, the thickness of the graphite anode active material layer is 10-20 μm.

4. The highly doped silicon-based anode sheet according to claim 1, characterized in that, Step S1 includes: mixing the first graphite active material and the silicon-based anode material evenly to obtain a composite anode material; adding the first conductive agent, the first binder, the second conductive agent and deionized water to the composite anode material in sequence, dispersing at high speed, then adding the second binder, dispersing evenly to obtain the first anode slurry; Step S2 includes: placing an aqueous binder in deionized water and stirring to obtain a negative electrode solution; adding a first conductive agent to the negative electrode solution and dispersing it at high speed to obtain a negative electrode conductive adhesive; adding a second graphite active material to the negative electrode conductive adhesive and dispersing it at high speed, then adding a second binder and dispersing it evenly to obtain a second negative electrode slurry.

5. The highly doped silicon-based anode sheet according to claim 1, characterized in that, The first conductive agent includes conductive carbon black; And / or, the first adhesive comprises a propylene polymer or a styrene-butadiene rubber adhesive; And / or, the second conductive agent includes one or more of single-walled carbon nanotubes, carbon fibers, and graphene; And / or, the second adhesive includes styrene-butadiene rubber-based adhesives; And / or, the aqueous binder includes carboxymethyl cellulose; And / or, in step S1, the amount of the first conductive agent added is 0.5%-1.0% of the mass of the composite negative electrode material; And / or, in step S1, the amount of the first binder added is 2.3%-6% of the total mass of the first conductive agent and the composite negative electrode material; And / or, in step S1, the amount of the second conductive agent added is 0.05%-0.1% of the total mass of the first conductive agent and the composite negative electrode material; And / or, in step S1, the amount of the second binder added is 1.0-2.5% of the total mass of the first conductive agent, the second conductive agent, the first binder, deionized water, and the composite negative electrode material; And / or, in steps S1 and S2, the dispersion rotation speed is 2000-4000 rpm and the time is 5-10 min.

6. The highly doped silicon-based anode sheet according to claim 4, characterized in that, The viscosity of the second negative electrode slurry is 2500-4000 mPa·s, and the solid content is 35%-45%; in step S2, the solid content of the negative electrode adhesive is 1.0-2.5%; And / or, in step S2, the amount of the first conductive agent added accounts for 0.5-2.0% of the mass of the negative electrode adhesive; And / or, in step S2, the amount of the second graphite active material added accounts for 95.3%-96.2% of the mass of the negative electrode conductive adhesive; And / or, in step S2, the amount of the second binder added accounts for 1.6-2.5% of the total mass of the second graphite active material and the negative electrode conductive adhesive; And / or, in step S3, the coating surface density of the first negative electrode slurry is 86-190 g / cm³. 2 ; And / or, in step S3, the coating surface density of the second negative electrode slurry is 35-45 g / cm³. 2 The drying temperature of the first negative electrode slurry is 70-85℃.

7. A lithium-ion battery, characterized in that, It includes a positive electrode, a highly doped silicon-based negative electrode as described in any one of claims 1-6, a separator, an electrolyte, and a casing.

8. A method for preparing a lithium-ion battery as described in claim 7, characterized in that, Includes the following steps: A high-mixed silicon-based negative electrode lithium-ion battery is manufactured by stacking, assembling, baking, liquid injection, formation, and capacity testing of a positive electrode sheet prepared from a positive electrode material and a high-mixed silicon-based negative electrode sheet as described in any one of claims 1-6 in sequence according to the order of separator-negative electrode-separator-positive electrode. The formation process includes: charging at 0.1-0.5C for 7-24 minutes, resting for 5 minutes, charging at 0.1-0.5C for 117-127 minutes, and achieving a formation SOC of 35%-40%.

Citation Information

Patent Citations

  • Graphite / silicon gradient electrode material and preparation method and fast charging application thereof

    CN114156458A

  • Negative plate, preparation method thereof and lithium ion battery

    CN115528204A